Old wine, new bottles and the Internet. (1st July 2014) - ,
Abstract : The Internet has given a new shape to modern capitalism. These new features have drawn the attention of numerous scholars and have become the focus of highly topical and controversial questions. However, as a rule, the literature has not taken as its starting point the development of a Marxist epistemology. The reason for this is the failure to derive a Marxist theory of knowledge from Marx's value theory. This is the task this article sets itself. The first section conceptualises mental versus objective labour processes and rejects the notion of the non-materiality of knowledge. The second section builds on this conceptualisation and deals with three interrelated questions, namely whether mental labour can produce value and surplus value and whether the distinctions on the one hand between productive and unproductive labour and on the other between production and consumption retain their validity in mental production. The third section explores the class nature of knowledge with particular reference to the Internet. Some final considerations follow in the last section.